СТРУКТУРНЫЙ АНАЛИЗ ИНФОРМАЦИОННО- КОММУНИКАЦИОННЫХ ТЕРМИНОВ В УЗБЕКСКОМ ЯЗЫКЕ - Зиямухамедова Ш. Т. (International Journal of Innovative Technologies in Social Science, 2019)
The article deals with the ICT and the language, their integration in the language usage. ICT newly become a vital part of the living, and the problem of creating equivalent word of foreign terminology in native language arises for the population and scientists of a country. Therefore, terminology and finding equivalents matter in the process of translation.